2018
DOI: 10.1212/wnl.0000000000006120
|View full text |Cite
|
Sign up to set email alerts
|

Psychophysic-psychological dichotomy in very early acute mTBI pain

Abstract: There appears to be a dichotomy between somatosensory and psychological findings in the very early acute post-mTBI stage; while the first is altered and is associated with the clinical picture, the second is unchanged. In the context of the ongoing debate on the pathophysiologic nature of the post-mTBI syndrome, our findings support its "physical" basis, free of mental influence, at least in the short time window after the injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 17 publications
3
27
0
Order By: Relevance
“…Similarly, in a crosssectional human study, our lab revealed decreased pressure pain thresholds of the head and decreased pain inhibition on the conditioned pain modulation (CPM) test in mild TBI patients within 2 weeks of injury compared to a non-mild TBI control group [13]. These results are in line with another study showing less efficient CPM in mild TBI patients within 72 h of the injury [14]. Furthermore, a cross-sectional human study demonstrated that mild TBI patients with chronic PTH (> 1 year post injury) exhibit diminished pain inhibitory capacity compared to control groups [15], with the magnitude of headache pain intensity correlating negatively with magnitude of pain inhibition.…”
Section: Introductionsupporting
confidence: 84%
“…Similarly, in a crosssectional human study, our lab revealed decreased pressure pain thresholds of the head and decreased pain inhibition on the conditioned pain modulation (CPM) test in mild TBI patients within 2 weeks of injury compared to a non-mild TBI control group [13]. These results are in line with another study showing less efficient CPM in mild TBI patients within 72 h of the injury [14]. Furthermore, a cross-sectional human study demonstrated that mild TBI patients with chronic PTH (> 1 year post injury) exhibit diminished pain inhibitory capacity compared to control groups [15], with the magnitude of headache pain intensity correlating negatively with magnitude of pain inhibition.…”
Section: Introductionsupporting
confidence: 84%
“…This is important as although oftentimes compared, post-traumatic and post-surgical pain represent 2 distinctive models for the study of acute pain, due in part to the cognitive attributions each may hold. We 19 have recently reported that these patients are psychologically similar to healthy controls in most pain-related psychological characteristics, which bolsters the likelihood that their results are generalizable. Given that most of the work regarding PSQ has been performed in the chronic stage, a preliminary goal was to examine the association between clinical and experimental pain and the PSQ in acute pain patients.…”
Section: Introductionsupporting
confidence: 55%
“…The chosen cohort of individuals with acute post-traumatic pain due to MVC offers a unique opportunity to explore pain variability in a setting in which there exists an interplay between clinical pain, contextual psychological factors, and the cognitive processes necessary to interpret and respond to the event. To that end, postinjury individuals with acute pain at the very early phase after injury, who were previously found to be psychologically similar to healthy controls, 19 were investigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A considerable limitation of the study is that Pain-60 is not an established test for evaluation bias, and that we did not use other tests for evaluation biases. Nonetheless, we do think that the measure of pain-50 or pain-60 temperature can potentially serve as a test for higher pain responsiveness; a recent study of our collaborators (22) demonstrated a lower Pain-50 temperature in patients with mild traumatic brain injury pain as compared with healthy controls. Thus, we believe that our finding on Pain-60 temperature as differentiating between the pain sensory-perceptual profile of patients suffering from major depression and healthy controls is not surprising.…”
Section: Discussionmentioning
confidence: 99%